**Well lets do some algebra!**

**\(a^3 + 3ab^2 = 679\)**

**\(a^3 - 3ab^2 = 673\)**

**\(a^3 + 3ab^2 = 679 \) this is equal to**

**\(a^3 - 3ab^2 = 679 - 6ab^2\)**

**we can conclude that**

**\(673 = 679 - 6ab^2\)**

\(6 = 6ab^2\)

\(ab^2 = 1\)

**Most likely a will be very big because we need a^3 to equal something large since the second term is = to 3.**

**so a^3 = 676 so a = \(\sqrt[3]{676}\)**

**b = \(\sqrt{\frac{1}{\sqrt[3]{676}}},-\sqrt{\frac{1}{\sqrt[3]{676}}}\)**

**a - b = \(\sqrt[3]{676}-\frac{1}{\sqrt{\sqrt[3]{676}}},\sqrt[3]{676}+\frac{1}{\sqrt{\sqrt[3]{676}}}\) that is so definenly incorrect, so plz someone see if this is correct or not**